2021
DOI: 10.3390/microorganisms9091842
|View full text |Cite
|
Sign up to set email alerts
|

The Rhizobial Microbiome from the Tropical Savannah Zones in Northern Côte d’Ivoire

Abstract: Over the past decade, many projects have been initiated worldwide to decipher the composition and function of the soil microbiome, including the African Soil Microbiome (AfSM) project that aims at providing new insights into the presence and distribution of key groups of soil bacteria from across the African continent. In this national study, carried out under the auspices of the AfSM project, we assessed the taxonomy, diversity and distribution of rhizobial genera in soils from the tropical savannah zones in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 142 publications
(174 reference statements)
0
12
0
Order By: Relevance
“…Major studies, led by the Earth Microbiome Project [ 7 ], have attempted to map both the microbial diversity and functional capacity of soil microbial communities across the globe by using a combination of sequence-based approaches, including taxonomic marker gene (e.g., 16S rRNA gene and ITS) DNA-barcoding approaches and more in-depth next-generation sequencing of total soil DNA (see Fierer (2017) for a comprehensive review [ 8 ]). These and many other more localized studies [ 9 – 13 ] have shown that a small percentage of microbial taxa dominate global soil microbial communities, with phyla such as the bacterial Acidobacteriota and Proteobacteria, the archaeal Crenarchaeota, and the fungal Ascomycota [ 14 17 ] being commonly found within soil microbiomes. However, contrary to the popular Baas-Becking hypothesis which states that “everything is everywhere, but the environment selects” [ 18 ], microecological surveys have shown that different biomes harbor distinct microbial communities that are shaped by both deterministic processes such as environment selection, as well as more stochastic events such as dispersal limitation [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major studies, led by the Earth Microbiome Project [ 7 ], have attempted to map both the microbial diversity and functional capacity of soil microbial communities across the globe by using a combination of sequence-based approaches, including taxonomic marker gene (e.g., 16S rRNA gene and ITS) DNA-barcoding approaches and more in-depth next-generation sequencing of total soil DNA (see Fierer (2017) for a comprehensive review [ 8 ]). These and many other more localized studies [ 9 – 13 ] have shown that a small percentage of microbial taxa dominate global soil microbial communities, with phyla such as the bacterial Acidobacteriota and Proteobacteria, the archaeal Crenarchaeota, and the fungal Ascomycota [ 14 17 ] being commonly found within soil microbiomes. However, contrary to the popular Baas-Becking hypothesis which states that “everything is everywhere, but the environment selects” [ 18 ], microecological surveys have shown that different biomes harbor distinct microbial communities that are shaped by both deterministic processes such as environment selection, as well as more stochastic events such as dispersal limitation [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated microbial community compositions, and the impact of environmental factors on microbiome composition, on a national, continental or global scale ( Fierer and Jackson, 2006 ; Delgado-Baquerizo et al, 2018 ; Karimi et al, 2018 ; Gnangui et al, 2021 ; Cowan et al, 2022 ). It has been shown that different environmental factors lead to different niches and the specific selection of a core microbiome ( Turnbaugh et al, 2007 ; Liu et al, 2018 ; Pajares et al, 2018 ; Koutika et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using high-throughput sequencing facilities to assess the functions and drivers of the core microbiome in soils have been conducted at small scale and at local levels ( Pershina et al, 2018 ; Jiao et al, 2022 ; Kolton et al, 2022 ). Recent studies of African soil microbiomics have attempted to map both the microbial diversity and functional capacity of soil microbial communities at a local ( Maquia et al, 2020 ; Gnangui et al, 2021 ) or continental scales ( Cowan et al, 2022 ). However, the authors are unaware of any biogeographical studies focusing on the causative relationships that may exist between environmental factors and the core soil microbiome structure in any sub-Saharan nation.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular techniques have evolved to the extent that researchers have been able to address deficiencies in understanding the genetic traits encoded by the genes located on the DNA or RNA molecule [5], through the use of molecular methods that are characterized by their relative ease, and their ability to track genes located on chromosomes and pSym plasmid in Rhizobium bacteria, which should lead to new insights into understanding the mechanisms of diversity and evolution in soils [6]. The polymerase chain reaction (PCR) is a method widely used in molecular biology, as it rapidly produces billions of copies of a specific sample of deoxyribonucleic acid, and this reaction includes DNA replication to determine the sequence, cloning and manipulating, mutating, and functional analysis of these genes [7], and agarose gel electrophoresis is the best way to separate DNA based on its sizes [8].…”
Section: Introductionmentioning
confidence: 99%